A water-soluble tetraazaperopyrene dye as strong G-quadruplex DNA binder - Hahn, Lena; Buurma, Niklaas Jan; Gade, Lutz H. (Chemistry - a European journal, 2016)
The interactions of the water-soluble tetraazaperopyrene dye 1 with ct-DNA, duplex-[(dAdT)12⋅(dAdT)12], duplex-[(dGdC)12⋅(dGdC)12] as well as with two G-quadruplex-forming sequences, namely the human telomeric 22AG and the promotor sequence c-myc, were investigated by means of UV/visible and fluorescence spectroscopy, isothermal titration calorimetry (ITC) and molecular docking studies. Dye 1 exhibits a high affinity for G-quadruplex structures over duplex DNA structures. Furthermore, the ligand shows promising G-quadruplex discrimination, with an affinity towards c-myc of 2×107 m−1 (i.e., Kd=50 nm), which is higher than for 22AG (4×106 m−1). The ITC data reveal that compound 1 interacts with c-myc in a stoichiometric ratio of 1:1 but also indicate the presence of two identical lower affinity secondary binding sites per quadruplex. In 22AG, there are two high affinity binding sites per quadruplex, that is, one on each side, with a further four weaker binding sites. For both quadruplex structures, the high affinity interactions between compound 1 and the quadruplex-forming nucleic acid structures are weakly endothermic. Molecular docking studies suggest an end-stacking binding mode for compound 1 interacting with quadruplex structures, and a higher affinity for the parallel conformation of c-myc than for the mixed-hybrid conformation of 22AG. In addition, docking studies also suggest that the reduced affinity for duplex DNA structures is due to the non-viability of an intercalative binding mode.